Current Outcomes and Indications for Cryopreserved Vein Allografts in Hemodialysis Access Surgery. Issue 1 (January 2016) - Jadlowiec, Caroline C.; Lavallee, Matthew; Mannion, Elizabeth M.; Lally, Anne; Rochon, Caroline; Sheiner, Patricia A.; Brown, Matthew G.
Introduction: Cryopreserved vein allografts (cadaveric vein) have emerged as an option for arteriovenous graft reconstruction; however, indications for their use in hemodialysis access remains to be clearly defined. Observations from our own experience have suggested that cadaveric vein grafts (CVGs) provide good outcomes, particularly in patients with a history of infection, recurrent access failure and advanced age. Methods: This is a 10-year retrospective study. Primary outcomes were (1 ) to identify characteristics specific to this patient population and (2 ) to better define indications for use of cadaveric vein in hemodialysis access creation. Results: Indications for creation of CVGs included patient history of either active or recent infection (41.5%), recurrent access failure (43.4%) or surgeon preference secondary to patients' advanced age (9.4%). Observed primary patency rates were 84.9% (30 days), 22.6% (1 year) and 16.0% (2 years). Secondary patency was 93.4% (30 days), 66.0% (1 year) and 52.8% (2 years). Patient death was the highest cause of graft abandonment (52.9%) followed by thrombosis (19.1%), infection (11.7%) and rupture (11.7%). CVG patency at the time of patient death was 83.7%. Conclusions: The rates of both primary and secondary patency in CVGs are highly comparable to the reported patency rates of polytetrafluoroethylene (PTFE) grafts and allow for lifelong maintenance of dialysis access. Our observed outcome suggests that CVGs should be considered for patients needing vascular access in the presence of infection. CVGs may likewise be viable alternatives to PTFE grafts in the elderly and patients with limited access options.